PENGARUH STRATEGI DIFERENSIASI PRODUK, STRUKTUR MODAL DAN CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE TERHADAP NILAI PERUSAHAAN DENGAN KEPEMILIKAN INSTITUSIONAL SEBAGAI VARIABEL MODERASI - Elisabet Elisabet; Susi Dwi Mulyani (Jurnal Magister Akuntansi Trisakti, 2018)
The purpose of this study was to examine the effect of Product Differentiation Strategy, Capital Structure and Corporate Social Responsibility Disclosure on Corporate Values with Institutional Ownership as Moderation variables in manufacturing companies listed on the Indonesia Stock Exchange. This study uses the Institutional Ownership variable as a moderating variable, namely to find out institutional ownership owned by the company. As well as this study using a variable company size which is used as a control variable, the relationship between dependent and independent variables. This study also aims to determine what factors have a significant effect on the value of the company. Based on the results of the analysis, it can be concluded that the Product Differentiation Strategy has a positive influence on Company Value, Capital Structure does not have a negative influence on the Corporate Value, Corporate Social Responsibility Disclosure does not have a positive influence on the Company's Value, Institutional Ownership has a positive influence on the Value of the Company, Institutional Ownership does not can strengthen the influence of the Product Differentiation Strategy on Company Value, Institutional Ownership cannot weaken the influence of Capital Structure on Company Value, Institutional Ownership cannot strengthen the influence of Corporate Social Responsibility Disclosure on Company Value.